Faktor Sosial Ekonomi dan Profitabilitas Usahatani Padi Sawah Tadah Hujan Kabupaten Maros - Arifin, Arifin; Zulkifli, Zulkifli; Azisah, Azisah; Sadat, Mohammad Anwar; Pata, Abdul Asis; Megawati, Megawati; Asriyani, Asriyani (Universitas Galuh, 2025)
Increases and decreases in production affect the income or profitability of farmers and welfare related to socio-economic conditions. The purpose of this study was to analyze socio-economic factors that affect profitability and the profitability of rainfed lowland rice farming. This research was conducted in Bontocabu Village, Lau District, and Bontobahari Village, Bontoa District, Maros Regency. The study was conducted in September - October 2024. The population of the study was 317 people, while the number of farmer samples used as respondents was 50 people. Sampling using multi-stage cluster random sampling technique. Data collection techniques used were observation, and interviews, while data sources were primary data and secondary data. Data analysis used multiple regression and quantitative description. The results of this study are socio-economic factors that affect the profitability of rainfed lowland rice farming are age, area of cultivation, and farming experience. Profitability was obtained at 62.18%. This shows that the profitability of rice farming is greater than the bank deposit interest rate (BRI 3%), meaning that rice farming is viable or profitable. As for the Break Event Point (BEP), a result of IDR. 367,589.18 was obtained. This shows that the value of BEP is smaller than the average revenue, which is IDR 8,087,580.00. This means that rice farming on rainfed rice fields is worth cultivating.